Long‐term outcomes of heart failure patients who received primary prevention implantable cardioverter‐defibrillator: An observational study. Issue 1 (26th December 2017) - Looi, Khang‐Li; Sidhu, Karishma; Cooper, Lisa; Dawson, Liane; Slipper, Debbie; Gavin, Andrew; Lever, Nigel
Abstract: Background: Implantable cardioverter‐defibrillator (ICD) therapy is indicated for selected heart failure patients for the primary prevention of sudden cardiac death. Little is known about the outcomes in patients selected for primary prevention device therapy in the northern region of New Zealand. Method: Heart failure patients with systolic dysfunction who underwent primary prevention ICD/cardiac resynchronization therapy‐defibrillator (CRT‐D) implantation between January 1, 2007, and June 1, 2015, were included. Complications, mortality, and hospitalization events were reviewed. Results: Three hundred and eighty‐five primary prevention devices were implanted (269 ICD, 116 CRT‐D). Mean age at implant was 59.1 ± 11.4 years. Mean duration of follow‐up was 3.64 ± 2.17 years. The commonest cause of death was heart failure (41.8%). Only 2 patients died from sudden arrhythmic death. The 5‐year heart failure mortality rate was 6%, whereas the 5‐year sudden arrhythmic death rate was 0.3%. Heart failure hospitalizations were commoner in those who received ICD than CRT‐D (67.7% vs 25.8%, P < .001). Maori patients have low implant rates (14%) with relatively high rates of admissions with heart failure and ventricular arrhythmia admissions, Conclusions: Even in appropriately selected heart failure patients who received primary prevention devices, only a small percentage died as a result of sudden arrhythmic death. CRT‐D should be the device of choice where appropriate in heart failure patients. Significant challenges remain to improve access to device therapy and maximize benefit to those who do get implanted.